The Implementation of The Competence Certification for Professional Welders at Smkn 2 Wonosari and Smkn 2 Pengasih - Syamsuddin, Arief; Prasetio, Widagdo Eka; Kuat, Tri (Universitas Ahmad Dahlan, 2021)
This study was aimed to describe and interpret the implementation of the competence certification for professional welders at SMKN 2 Wonosari and SMKN 2 Pengasih which included: (1) the administrators’ readiness, (2) the implementation, (3) the supporting and obstacles factors, and (4) the impact of the program of competence certification for professional welders for learner outputs at SMKN 2 Wonosari and SMKN 2 Pengasih. This research used phenomenological qualitative approach. The subjects were the principal, the teachers, the committee of certification program, and the assessors. To collect the data, the researcher conducted interviews, observation, and analyzing the documents on the subject of the research. The results of the study show that the implementation of the competence certification for professional welders in terms of : (1) The administrators’ readiness had been appropriate with the stages of the certification process; (2) The implementation of the program went well according to the schedule at the stage of plan, implementation, and evaluation; (3) Supporting factors in the implementation of the program has been well supported with the form of moral and material as well as inhibiting factors is the lack of funds to repair facilities and infrastructure; (4 ) Impact of welding competence certification program for the learner outputs embedded in increasing learner outputs' achievements, confidence, and easiness to get their jobs at the company and earn higher salary.